Differential infectivity of gametocytes after artemisinin-based combination therapy of uncomplicated falciparum malaria - Dinkorma T. Ouologuem; Cheick O. Kone; Bakary Fofana; Bakary Sidibe; Amadou H. Togo; Demba Dembele; Sekou Toure; Sekou Koumare; Ousmane Toure; Issaka Sagara; Abdoulaye Toure; Adama Dao; et al. (AOSIS, 2018)
Background: Most malaria-endemic countries use artemisinin-based combination therapy (ACT) as their first-line treatment. ACTs are known to be highly effective on asexual stages of the malaria parasite. Malaria transmission and the spread of resistant parasites depend on the infectivity of gametocytes. The effect of the current ACT regimens on gametocyte infectivity is unclear. Objectives: This study aimed to determine the infectivity of gametocytes to Anopheles gambiae following ACT treatment in the field. Methods: During a randomised controlled trial in Bougoula-Hameau, Mali, conducted from July 2005 to July 2007, volunteers with uncomplicated malaria were randomised to receive artemether-lumefantrine, artesunate-amodiaquine, or artesunate-sulfadoxine/pyrimethamine. Volunteers were followed for 28 days, and gametocyte carriage was assessed. Direct skin feeding assays were performed on gametocyte carriers before and after ACT administration. Results: Following artemether-lumefantrine treatment, gametocyte carriage decreased steadily from Day 0 to Day 21 post-treatment initiation. In contrast, for the artesunate-amodiaquine and artesunate-sulfadoxine/pyrimethamine arms, gametocyte carriage increased on Day 3 and remained constant until Day 7 before decreasing afterward. Mosquito feeding assays showed that artemether-lumefantrine and artesunate-amodiaquine significantly increased gametocyte infectivity to Anopheles gambiae sensu lato (s.l.) (p < 10−4), whereas artesunate-sulfadoxine/pyrimethamine decreased gametocyte infectivity in this setting (p = 0.03). Conclusion: Different ACT regimens could lead to gametocyte populations with different capacity to infect the Anopheles vector. Frequent assessment of the effect of antimalarials on gametocytogenesis and gametocyte infectivity may be required for the full assessment of treatment efficacy, the potential for spread of drug resistance and malaria transmission in the field.